HINDU DALAM WACANA MODERASI BERAGAMA: (Membangun Puncak Kesadaran Berketuhanan) - Putu Dana Yasa; Kadek Agus Wardana (UHN IGB Sugriwa Denpasar, 2023)
The debate about religious differences seems to have become a deep-rooted problem, its roots have gone deep into the ground so that it is very difficult to uproot. Religious debates seem to have found no common ground and are actually getting heated up due to the emergence of judgments against different beliefs or religions, this condition seems to position one belief as right while another belief is wrong. With this condition, diverse awareness is needed with a moderate attitude in accordance with the discourse that has been conveyed quite often lately. As part of a recognized belief in Indonesia, Hinduism actually has various concepts in an effort to live in harmony in the midst of existing differences. The various concepts possessed by Hinduism are not only a discourse for moderate, peaceful and harmonious life, but this concept teaches Hindus to be able to grow the peak of divine awareness by realizing that all creatures that exist are manifestations of God. So that there is no reason for Hindus to judge other people let alone feel right and always blame other people's religion Keywords: Hinduism, Moderation, Divinity Awareness